2021
DOI: 10.3389/fmolb.2021.682594
|View full text |Cite|
|
Sign up to set email alerts
|

CORO1C is Associated With Poor Prognosis and Promotes Metastasis Through PI3K/AKT Pathway in Colorectal Cancer

Abstract: Trophoblast cell surface protein 2 (Trop2) is one of the cancer-related proteins that plays a vital role in biological aggressiveness and poor prognosis of colorectal cancer (CRC). The study of the Trop2 related network is helpful for us to understand the mechanism of tumorigenesis. However, the effects of the related proteins interacting with Trop2 in CRC remain unclear. Here, we found that coronin-like actin-binding protein 1C (CORO1C) could interact with Trop2 and the expression of CORO1C in CRC tissues was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Interestingly, metastatic cells are rich in filopodia-like structures [ 34 ]. Recently, TROP2-interacting proteins were linked to matrix degradation, cell shape, motility, and invasion in CRC cells [ 35 ]. We found that under adhesion blockade, ATF2-KO cells built only vital single cells or small aggregates, and that transient TROP2 silencing attenuated this de-adhesive effect, which was accompanied by a loss in cell–cell protrusions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, metastatic cells are rich in filopodia-like structures [ 34 ]. Recently, TROP2-interacting proteins were linked to matrix degradation, cell shape, motility, and invasion in CRC cells [ 35 ]. We found that under adhesion blockade, ATF2-KO cells built only vital single cells or small aggregates, and that transient TROP2 silencing attenuated this de-adhesive effect, which was accompanied by a loss in cell–cell protrusions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, primary fibroblasts derived from Coronin1C-deficient mice display impaired cell migration and protrusion formation through abnormal actin filaments, microtubules, and intermediate filaments [ 26 ]. The involvement of Coronin1C in migration, invasion, and metastatic abilities has been observed in various cancer cells, such as human gastric cancer cells [ 15 , 27 , 28 ], melanoma cells [ 29 ], breast cancer cells [ 30 , 31 ], hepatocellular carcinoma cells [ 32 ], glioblastoma cells [ 33 ]. Thus, the actin-binding protein Coronin1C is commonly involved in cell motility, including migration, invasion, and chemotaxis in many cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins involved in the PI3K/Akt pathway are abnormally expressed in several tumors, thereby leading to the progression of breast, gastric, nasal and pancreatic cancers, among others 35–37 . This pathway is closely associated with tumor proliferation, autophagy and migration 38–40 . Therefore, research on ADAMDEC1 and whether it targets the PI3K/AKT pathway may have great significance in the management of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“… 35 , 36 , 37 This pathway is closely associated with tumor proliferation, autophagy and migration. 38 , 39 , 40 Therefore, research on ADAMDEC1 and whether it targets the PI3K/AKT pathway may have great significance in the management of NSCLC. Here, we demonstrate that PI3K/AKT is critically involved in the regulation of ADAMDEC1 expression to maintain cancer cell survival and proliferations.…”
Section: Discussionmentioning
confidence: 99%